2013
DOI: 10.7314/apjcp.2013.14.8.4775
|View full text |Cite
|
Sign up to set email alerts
|

GPR48 Promotes Multiple Cancer Cell Proliferation via Activation of Wnt Signaling

Abstract: The key signaling networks regulating cancer cell proliferation remain to be defined. The leucine-rich repeat containing G-protein coupled receptor 48 (GPR48) plays an important role in multiple organ development. In the present study, we investigated whether GPR48 functions in cancer cells using MCF-7, HepG2, NCI-N87 and PC-3 cells. We found that GPR48 overexpression promotes while its knockdown using small interfering RNA oligos inhibits cell proliferation. In addition, Wnt/β-catenin signaling was activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
17
1
Order By: Relevance
“…LRG4 induces, when bound by RANKL, inhibition of osteoclast differentiation which is in contrast with the effect of binding of RANKL to RANK. Although the exact relationship between LRG4 and cancer is not clear yet, it was shown that it is involved in the proliferation of several tumor cell lines [98]. Hence, future studies should also bear in mind the potential interactions between RANKL and LRG4.…”
Section: An Anti-tumor Effect Of Rankl Inhibition Mediated Via the Immentioning
confidence: 99%
“…LRG4 induces, when bound by RANKL, inhibition of osteoclast differentiation which is in contrast with the effect of binding of RANKL to RANK. Although the exact relationship between LRG4 and cancer is not clear yet, it was shown that it is involved in the proliferation of several tumor cell lines [98]. Hence, future studies should also bear in mind the potential interactions between RANKL and LRG4.…”
Section: An Anti-tumor Effect Of Rankl Inhibition Mediated Via the Immentioning
confidence: 99%
“…[17] Transfection of ARPE-19 cells with a specific LGR4 siRNA significantly reduced LGR4 protein level after 72 hours (Fig 2A). Based on the MTS cell proliferation assay and Ki67 immunostaining results, LGR4 siRNA significantly inhibited growth of ARPE-19 cells three days after transfection (Fig 2B and 2C).…”
Section: Resultsmentioning
confidence: 99%
“…[17,20] p27 Kip1 induced LGR4 upregulation can enhance colon cancer progression and metastasis. [19] LGR4 promotes prostate tumorigenesis through PI3K/Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the LGR4 receptor promotes cancer cell proliferation in multiple cell types through activation of the Wnt signaling cascade [95,96]. In cervical carcinoma cells, it correlates with enhanced cell migration and metastasis [97].…”
Section: Prognostic Value Of Lgrsmentioning
confidence: 99%